Surface Morphologies in a Mars-Analog Ca-Sulfate Salar, High Andes, Northern Chile - Hinman, Nancy W.; Hofmann, Michael H.; Warren-Rhodes, Kimberly; Phillips, Michael S.; Noffke, Nora; Cabrol, Nathalie A.; Chong Diaz, Guillermo; Demergasso, Cecilia; Tebes-Cayo, Cinthya; Cabestrero, Oscar; Bishop, Janice L.; Gulick, Virginia C.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Salar de Pajonales, a Ca-sulfate salt flat in the Chilean High Andes, showcases the type of polyextreme environment recognized as one of the best terrestrial analogs for early Mars because of its aridity, high solar irradiance, salinity, and oxidation. The surface of the salar represents a natural climate-transition experiment where contemporary la-goons transition into comprises lagoons, infrequently inundated areas, salt crusts, and lastly dry exposed paleoterraces creating a natural climate-transition experiment. These individual surface features on the salar represent different evolutionary stages of evolution in the transition from previously wetter climatic conditions to much drier conditions persisting today. These same stages closely mirror the climate transition on Mars from a wetter early Noachian to the Noachian/Hesperian. Therefore, the Salar de Pajonales thus provides a unique window into what the last near-surface oases for microbial life on Mars could have been like in hypersaline environments as the climate changed and water disappeared from the surface. Here we open that climatological window by evaluating the narrative recorded in the salar surface morphology and mi-croenvironments and extrapolating to similar paleosettings on Mars. Our observations suggest a strong inter-dependencey between small and large scale features that we interpret to be controlled by extrabasinal changes in environmental conditions, such as precipitation-evaporation-balance changes and thermal cycles, and most importantly, by internal processes, such as hydration/dehydration, efflorescence/deliquescence, and recrystallization brought about by physical and chemical processes related to changes in groundwater recharge and volcanic processes. Surface structures and textures record a history of hydrological changes that impact the mineralogy and volume of Ca-sulfate layers comprising most of the salar surface. Similar surface features on Mars, interpreted as products of freeze-thaw cycles, could, instead, be products of water-driven, volume changes in salt deposits. On Mars, surface manifestations of such salt-related processes would point to potential water sources. Because hygroscopic salts have been invoked as sources of localized, transient water sufficient to support terrestrial life, such structures might be good targets for biosignature exploration on Mars.